Usaha Keripik Lokal : Kisah Inspiratif di Balik Rasa, Tantangan, dan Kesuksesan di Desa Sugiharjo Kecamatan Batang Kuis - Vina Aulia; Angelina Sipayung; Ramadhan Fitriani; Muhammad Ridha Syafii Damanik; Syukrie Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to examine in more depth the business journey, challenges and strategies for developing the local chips business in Sugiharjo Village, Batang Kuis District, Deli Serdang Regency. The local chips business is a popular economic choice because of the easy availability of raw materials and stable market demand. This research uses qualitative methods with a field observation approach and structured interviews. The research results show that despite facing various challenges such as limited capital and fluctuations in raw material prices, this chips business was able to develop thanks to innovation in the production process and digital marketing strategies. This research concludes that the success of a local chips business depends on technological adaptation, appropriate marketing strategies, and efficient resource management. It is hoped that these findings can contribute to local culinary MSMEs in facing challenges and developing their businesses.